CCL2 chemokine inhibition primes the tumor vasculature for improved nanomedicine delivery and efficacy - Möckel, Diana; Bartneck, Matthias; Niemietz, Patricia; Wagner, Maike; Ehling, Josef; Rama, Elena; Weiler, Marek; Gremse, Felix; Eulberg, Dirk; Pola, Robert; Pechar, Michal; Etrych, Tomas; et al. (Journal of controlled release, 2024)
Blood vessel functionality is crucial for efficient tumor-targeted drug delivery. Heterogeneous distribution and perfusion of angiogenic blood vessels contribute to suboptimal accumulation of (nano-) therapeutics in tumors and metastases. To attenuate pathological angiogenesis, an L-RNA aptamer inhibiting the CC motif chemokine ligand 2 (CCL2) was administered to mice bearing orthotopic 4T1 triple-negative breast cancer tumors. The effect of CCL2 inhibition on tumor blood vessel functionality and tumor-targeted drug delivery was evaluated via multimodal and multiscale optical imaging, employing fluorophore-labeled polymeric (10 nm) and liposomal (100 nm) nanocarriers. Anti-CCL2 treatment induced a dose-dependent anti-angiogenic effect, reflected by a decreased relative blood volume, increased blood vessel maturity and functionality, and reduced macrophage infiltration, accompanied by a shift in the polarization of tumor-associated macrophages (TAM) towards a less M2-like and more M1-like phenotype. In line with this, CCL2 inhibitor treatment improved the delivery of polymers and liposomes to tumors, and enhanced the antitumor efficacy of free and liposomal doxorubicin. Together, these findings demonstrate that blocking the CCL2-CCR2 axis modulates TAM infiltration and polarization, resulting in vascular normalization and improved tumor-targeted drug delivery.
Keywords: Neoplasms; nádory; makrofágy; Animals; Ligands; nádorové buněčné linie; Nanomedicine; chemokin CCL2; zvířata; Mice; Macrophages; Cell Line, Tumor; nanomedicína; Chemokine CCL2; ligandy; myši